Prevalence of periodontitis cases in the dental clinic Puskesmas Kerambitan II Tabanan periode October 2024-March 2025: Prevalensi kasus periodontitis di poli gigi Puskesmas Kerambitan II di Tabanan periode Oktober 2024 hingga Maret 2025 - Yuniari Dewi; I Wayan Agus Wirya Pratama; Ni Putu Ary Wahyu Suryani (Makassar Dental Journal, 2026)
Registration data for dental and oral services at the Kerambitan II Community Health Centre for the period October 2024-March 2025 shows that periodontal disease cases rank second among the highest diseases. Periodontitis is an inflammation and infection that occurs in the periodontal tissue and alveolar bone supporting the teeth. This descriptive study provides an overview of the prevalence of periodontitis cases among dental clinic visitors at the Kerambitan II Com-munity Health Centre from October 2024 to March 2025. The total population consisted of all visitors who had their teeth checked at the dental clinic, and the sample consisted of patients suffering from periodontitis. From the analysis of periodontal disease prevalence data based on gender, the highest prevalence was found in males (56.61%). It was concluded that periodontitis occurred among dental clinic visitors at the Kerambitan II Community Health Centre in Ta-banan from October 2024 to March 2025, with 189 sufferers, predominantly males at 56.61%. This is likely due to males having more unhealthy habits such as smoking and drinking alcohol.